Ideologi dalam Pesan Natal 2023: Pendekatan Analisis Wacana Kritis dalam Perspektif Fairclough: Ideology in Christmas messages 2023: a critical discourse analysis approach in Fairclough's perspective - Kabanga, Lewi (Journal of Literature and Education, 2024)
A different wave of uniqueness characterizes Christmas celebrations after the Covid-19 era compared to pre-pandemic celebrations. Every year, Christmas is accompanied by a consistent message theme. The Christmas message of 2023 from the Communion of Churches in Indonesia (PGI) and the Indonesian Church Guardian Conference (KWI) is closely related to the challenges faced by the nation, becoming the basis for the people in honoring God. This research explores the socio-cultural nuances contained in these Christmas messages. With a descriptive qualitative approach, this research uses Fairclough's critical discourse analysis framework and a theological perspective. Data obtained from internet downloads was reduced to identify key analysis elements. The analysis was conducted through three stages of Fairclough's model: text analysis, including description, interpretation, and explanation; discursive practices; and socio-cultural contextualized experience. Findings indicate the presence of eleven keywords in the Easter message, featuring linguistic diversity, including repetition, imperative language, persuasion, and causation. In addition, the socio-cultural insights highlighted caution towards election preparation, identity politics, environmental preservation, the impact of globalization, vigilance in using social media, and technological advancement. These Christmas messages are hoped to appropriately shape people's attitudes to create inner peace and prosperity in honoring God.